PEMBUATAN MESIN PROFIL (ROUTER) STATIS UNTUK INDUSTRI KECIL MEBEL KA YU - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The voucher program entitled "Manufacturing Static Profiling Machine(Router) for Small Wood Furniture Industries" aims to increase productivity of the Indah Jaya wood furniture industry especially in profile production of the produced furniture. It also wants to know the capacity and productivity of such static router machine.The steps of this manufacturing static router machine are planning,machine manufacturing, and training for industry partner workers. The planning step includes : (l) designing machine plan draft, (2) calculating the needed materials, and (3) calculating the implementation cost. The machine manufacturing step includes : (1) material cutting to fit the work draft, (2) welding, (3) assembling, (4) electric installation. (5) machine performance test, and (6) painting. The training for industry partner workers consists of: (1) theory and speech delivery, (2) demonstration of machine using, and (3) mahcine using practice by the industry partner workers.The result of the voucer program is realization of a static router machine and skill acievement by the industry partner workers in the machine operation. The static router machine was made of right-angled iron frame sizing 50x50x5 mm combined with steel plate of 3 mm thick. The machine is in 120x80x60 cm size moved by an electric motor power, SEM, of 0,5 HP and rotation speed of2800 RPM. The machine performance and productivity especially formanufacturing straight and curved, profiles for 9 mm size of meranti, kamper, and teak wood, is twice in speed as that of protable machines. If it is compared to that of manual profile planner, for manufacturing profiles with the same form and size, the router machine has five times in speed. Key words: profile machine, small industry, and wood furniture.